Principal Policy in Improving the Quality of Education MAN 1 Yogyakarta - Muchamad Arif Kurniawan Arif; Willa Putri; Krisna Ardawinata (al-Afkar, Journal For Islamic Studies, 2023)
This article discusses the policy of school principals in improving the quality of education, which is located in this research at MAN 1 Yogyakarta. This research method uses a descriptive qualitative method. As for collecting data, researchers used observation and interviews. The subjects of this research are school principals and teachers. The results of this study indicate that policies are made through the stages of policy formulation, policy implementation and policy evaluation. Meanwhile, through the formulation of policies made by the school principal, several policy agendas are produced such as improving infrastructure, developing human resources, implementing school programs that are both academic and non-academic. Of the several policies made, of course, they are oriented to the quality to be achieved by the institution.